Fatty Acid Binding Protein 11a Is Required for Brain Vessel Integrity in Zebrafish - Zhang, Jie; Qi, Jialing; Wu, Shuilong; Peng, Lijiao; Shi, Yunwei; Yang, Jinxian; Yin, Zhenhua; Gao, Yu; Wang, Chengniu; Gong, Jie; Zhang, Haijun; Zhang, Jingjing; et al. (Frontiers in Physiology, 2017)
The monolayer of endothelial cells lining the intima of all blood vessel wall forms a semipermeable barrier that regulates tissue-fluid homeostasis, transport of nutrients, and migration of blood cells across the barrier. A number of signaling pathways and molecules mediate endothelial permeability, which plays important roles in a variety of the physiological and pathological conditions. Fatty acid binding proteins (FABPs) are able to bind various hydrophobic molecules, such as long-chain fatty acids, prostaglandins and eicosanoids. FABP4, a member of the family of FABPs, plays an important role in maintenance of glucose and lipid homeostasis as well as angiogenesis. In the present study, we found that fabp11a, the ortholog of mammalian FABP4, was highly expressed in developing brain vessels of zebrafish. Knockout of fabp11a gene caused hemorrhage in zebrafish brain. Morpholino mediated fabp11a gene knockdown phenocopied the hemorrhage in mutants. Furthermore, we demonstrated permeability of brain vessels in fabp11a mutant is significantly higher than that of control. In addition, COX and LOX inhibition partially rescued the brain vessel integrity defects caused by fabp11a loss-of-function, suggesting the integrity defect was relevant to the Fatty Acid function.